Prohibition Of Religious Customs And Ceremonies During The Soviet Government - Jumaev Bekzod (Genius Journals, 2024)
In this article, the policy of the Soviet ideology towards religion, its influence on the local regions, the prohibition of Islamic rituals, etc., are highlighted
Keywords: religion; tradition; ritual